2021
DOI: 10.1186/s12888-021-03195-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical haemodynamic response during the verbal fluency task in patients with bipolar disorder and borderline personality disorder: a preliminary functional near-infrared spectroscopy study

Abstract: Background Functional near-infrared spectroscopy (fNIRS) is an emerging neuroimaging modality that provides a direct and quantitative assessment of cortical haemodynamic response during a cognitive task. It may be used to identify neurophysiological differences between psychiatric disorders with overlapping symptoms, such as bipolar disorder (BD) and borderline personality disorder (BPD). Hence, this preliminary study aimed to compare the cerebral haemodynamic function of healthy controls (HC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…It is separately reported that pro‐cognitive strategies in major depressive disorder resulted in improved overall functioning 50,51 . Additional research is required to parse the underlying neurobiological substrates that subserve measures of cognition 52,53 . Although preliminary evidence exists 54,55 for treatments that can improve aspects of social cognition, there is a need for scalable, cost‐effective intervention for social cognition in BD that can be implemented at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…It is separately reported that pro‐cognitive strategies in major depressive disorder resulted in improved overall functioning 50,51 . Additional research is required to parse the underlying neurobiological substrates that subserve measures of cognition 52,53 . Although preliminary evidence exists 54,55 for treatments that can improve aspects of social cognition, there is a need for scalable, cost‐effective intervention for social cognition in BD that can be implemented at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar disorder (BD) is a chronic mental illness characterized by an alternation between mania or hypomania and depression [1][2][3][4]. It is often associated with impaired functionality [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A WHO epidemiological survey found that the prevalence of BPD in the general population was 1.5% (Huang et al, 2009), while the prevalence of BPD accounted for about 25% among inpatients with mental disorders (Bozzatello et al, 2020). Clinical signs include affect dysregulation, impulsive aggression, repeated self-harm and chronic suicidal tendencies (Keng et al, 2019;Lieb et al, 2004). Husain et al(Husain et al, 2021 found widespread disruption of prefrontal cortex activity in patients with BPD through functional near infrared spectroscopy (fNIRS), which may contribute to their unstable emotion and impulsivity.…”
mentioning
confidence: 99%